Analisis Financial Technology dan Demografi Terhadap Tingkat Pengelolaan Keuangan Rumah Tangga - Rifki Khoirudin; Firsty Ramadhona Amalia Lubis (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2021)
One of the business operations that has begun to transform into digital is the financial or financial sector. This also affects people's behavior in using fintech. The purrpose of this study was to anallyze the tendency of changes in household financial management behavior. The reseaarch method used was the Ordinal logit regression analysis. The anallysis tool used is SPSS 25.0. The research data used is primary data with the type of cross section data. Samples were taken from 4 districts and 1 city located in the Province of Yogyakarta, Yogyakarta Special Region. The number of respondennts in this study were 102 respondents. The sampling method used was purposive sampling. The results of the study level of household financial management among the people of Yogyakarta is relatively good. Partially, age and education variables do not have a significant effect on the level of household financial management. The interesting thing that was found in this study was the variable use of fintech services did not have a significant effect on the level of household financial management. This means that easy access to finance through sophisticated financial technology does not make someone more consumptive. Profession variable has a negative and significant effect on the level of household financial management.